Abnormal expression of glucose-6-phosphatase in preterm infants. Issue 2 (February 1993) - Hume, R; Burchell, A
Abstract : The hepatic microsomal glucose-6-phosphatase enzyme was studied in liver samples from 76 premature infants including 15 victims of sudden infant death syndrome. The data obtained were compared with glucose-6-phosphatase activity in liver samples from 95 term infants. In the majority of preterm infants up to 350 days of age the activity of the glucose-6-phosphatase enzyme was at or below the extreme low limit of the normal range in term infants. The premature infants with the lowest hepatic microsomal glucose-6-phosphatase activities are likely to be at risk of hypoglycaemic episodes during periods of relative starvation or stress.